Improved Thermal Stability of Radiation Degradative Poly(methyl methacrylate) by Blending with Poly(ethylene glycol) - Al-Gahtany, S. Ali; Alshangiti, D. Mohamed; Madani, M.; Ghobashy, M. Mohamady (Asian Journal of Chemistry, 2020)
A blend polymer consists of poly(methyl methacrylate) (PMMA) and poly(ethylene glycol) (PEG) in four ratios 20:0, 18:2, 16:4 and 14:6. The blend polymer (PMMA/PEG) was characterized by using differential scanning calorimetry (DSC), TGA and FTIR. FTIR analysis proved that the lack of miscibility and interactions between PMMA (hydrophobic) and PEG (hydrophilic) were not due to hydrogen bonding but gamma irradiation at doses up to 20 kGy. Furthermore, DSC thermograms of the blend polymers display a positive deviation during the glass transition temperature (Tg) of PMMA due to gamma irradiation-induced PEG crosslinking, decreasing the molecular motion and chain relaxation between the two polymers. Blends that are not irradiated show negative Tg deviation from the corresponding values due to plasticization of PEG. Furthermore, the melting point (Tm) of PMMA increased with an increase in PEG, which acts as a filler at high temperatures.